The Parameters of the Field Emission Model and the Fabrication of Zinc Oxide Nanorod Arrays/Graphene Film - Yang, JianJun; Shao, ShuangShuang; Li, YaXin; Wang, YueHui; Feng, Chi (Frontiers in Physics, 2021)
A large-scale growth of zinc oxide (ZnO) nanorod arrays on graphene sheets were fabricated by hydrothermal technique, and the Fowler-Nordheim theory was used to build a model to describe the properties of the arrays’ field emission. The results indicated that the morphological characteristics of the ZnO nanorods grown on the graphene sheets can be easily tuned by varying the reaction time and concentrations of the reaction solution. The regular ordered ZnO nanorods arrays on the graphene sheets were obtained under the appropriate experimental conditions. Further, this composite cathode was demonstrated to possess excellent field emission properties due to the outstanding mechanical and electrical properties of the graphene. The field emission current density of the composite cathode reached 1448 μA/cm2 at the electric field of 16.5 V/μm. The key parameter,field enhancement factor, reached 6366, while the pure graphene cathode field is about 1660. These specific nanorod arrays with enhancement of the field emission properties would be useful to sensor or modulator units for access networks.